Clinical implications of the eighth edition of the American Joint Committee on Cancer melanoma staging. Issue 2 (21st December 2018) - Crompton, Joseph G.; Gilbert, Elizabeth; Brady, Mary S.
Abstract : The new edition of the American Joint Committee on Cancer staging system for melanoma builds on the foundation of prior editions but has several important improvements. The availability of regional nodal staging using sentinel lymph node biopsy (with subsequent follow‐up) has resulted in more accurate prognostication for patients and clinicians. This facilitates identification of those at higher risk for recurrence, and allows for the appropriate selection of patients for new adjuvant therapy and clinical trials. Although more complex than previous editions, the eighth edition will provide granularity to outcome analysis based on more precise risk stratification.